소아암 청소년의 입원 전·후 수면양상과 수면장애 요인 - 정진(Jung, Jin); 이은혜(Lee, Eun-Hye); 양유진(Yang, You-Jin); 장보윤(Jang, Bo-Yoon) (Asian oncology nursing, 2017)
Purpose: This is a descriptive study conducted in order to survey sleep patterns and factors responsible for sleep disturbance among adolescent cancer patients after hospital admission. Methods: The study group included 46 adolescent cancer patients aged 10 to 19 who received admission care in multi-bed hospital rooms from March to June 2016. Data on patterns and quality of sleep, and factors causing sleep disturbance were recorded using the Verran and Snyder-Halpern (VSH) Sleep Scale, the Pittsburgh Sleep Quality Index (PSQI), and a sleep disturbance questionnaire. Results: There was no difference in patterns and quality of sleep prior to and after hospital admission in the study group. However, patients experienced sleep disturbance, as defined by PSQI > 5, both before (5.43) and after (6.30) admission. The most important physical, emotional and environmental factors causing sleep disturbance after admission were nocturnal diuresis, monotony of admission care, and crying of younger patients respectively. Conclusion: This study focused on sleep patterns and factors causing sleep disturbance after hospital admission for adolescent cancer patients. Future studies should aim to develop nursing interventions resulting in an environment that improves sleep quality. Additional studies should focus on developing daytime programs to determine the impact of admission care on other quality of life parameters. KCI Citation Count: 1